Production of Neurospheres from CNS Tissue - Marshall, Gregory P. (Methods Mol Biol, 2008)
The relatively recent discovery of persistent adult neurogenesis has led to the experimental isolation and characterization of central nervous system neural stem cell populations. Protocols for in vitro analysis and expansion of neural stem cells are crucial for understanding their properties and defining characteristics. The methods described here allow for cell and molecular analysis of individual clones of cells—neurospheres—derived from neural stem/progenitor cells. Neurospheres can be cultivated from a variety of normal, genetically altered, or pathological tissue specimens, even with protracted postmortem intervals, for studies of mechanisms underlying neurogenesis, cell fate decisions, and cell differentiation. Neurosphere-forming cells hold great promise for the development of cell and molecular therapeutics for a variety of neurological diseases.